Investigation of auto-ignition of octane-CNG mixture in HCCI engine - Firmansyah, (Universiti Malaysia Pahang, 2015)
Homogeneous Charge Combustion Ignition (HCCI) operating principles have been widely investigated, yet the uncontrollable combustion of HCCI is the major obstacle in its development. The combustion characteristics of single fuels have been widely investigated as the fuel is the most influential factor that determines the HCCI combustion behavior. However, investigations of auto-ignition behavior for multiple fuels have not been carried out. This paper investigates various fuel compositions of Octane and compressed natural gas (CNG), ranging from 10-100 Octane/CNG. The investigation was done in a constant volume chamber with an 820 Â°C cartridge heater. Three lambdas were tested for each fuel mixture, namely 0.8, 1, and 1.2. From the results, it was found that the mixture composition has a major effect on the output of the combustion of dual fuel and a 20 ms injection gap shows better combustion results due to the higher percentage of Octane in the hotter regions, as well as the more homogeneous mixture created. On the other hand, the lambda is a significant parameter that affects the ignition delay, along with the temperature and droplet size of the mixture. Â© Universiti Malaysia Pahang.